PEMBAGIAN HARTA BERSAMA DENGAN SUAMI YANG TIDAK MEMBERIKAN NAFKAH - Firdaus, Seilla Nur Amalia; Sar'an, Mohamad; Zuhri, Nur Alam Ullumuddin; Albana, Rifki Hasan (JURNAL HAKAM, 2024)
The result of the breakdown of marriage is often a dispute over joint property. Article 97 KHI regulates the division of joint property with each party half a share. However, the reality in the field is not always the case, as in Decision Number 1349/Pdt.G/2023/PA.Bm the judge decided to divide it not equally, namely 40% for the husband and 60% for the former wife. The size of the ex-wife's share is because the ex-husband does not carry out his obligations as head of the family, namely providing maintenance. The difference in the percentage of the division of joint property makes the author interested in researching the decision. This research is a type of normative research with library research. Primary data sources are obtained from decision number 1349/Pdt.G/2023/PA.Bm and secondary data comes from books, journals, and so on. Data collection techniques using literature study with descriptive data analysis. The results of the study state that Decision Number 1349/Pdt.G/2023/PA.Bm according to the author is not in accordance with the theory of distributive justice initiated by Aristotle because the Defendant (ex-wife) who has a double burden as a housewife and works to earn a living does not get her rights as she should.Keywords :  joint property, family maintenance, distributive justice